On‐clamp versus off‐clamp partial nephrectomy: Propensity score‐matched comparison of long‐term functional outcomes. (24th July 2019) - Simone, Giuseppe; Capitanio, Umberto; Tuderti, Gabriele; Presicce, Fabrizio; Leonardo, Costantino; Ferriero, Mariaconsiglia; Misuraca, Leonardo; Costantini, Manuela; Larcher, Alessandro; Minisola, Francesco; Guaglianone, Salvatore; Anceschi, Umberto; et al.
Abstract : Objectives: To compare long‐term functional outcomes of off‐clamp or on‐clamp partial nephrectomy patients of two high‐volume centers with cT1–2/N0 M0 renal tumors and baseline estimated glomerular filtration rate >60 mL/min. Methods: A 3:1 propensity score‐matched analysis was used to select two homogeneous cohorts to compare off‐clamp versus on‐clamp partial nephrectomy. Joinpoint regression analysis was used to compare the 2–8‐year probabilities of estimated glomerular filtration rate modifications in both selected cohorts. The Kaplan–Meier method assessed the risk of developing a stage ≥3b chronic kidney disease during follow up. Multivariable analyses aimed to identify predictors of renal function deterioration. Perioperative complications and oncological outcomes were compared. Results: Overall, 1073 patients were included (588 on‐clamp and 485 off‐clamp). After applying the propensity score‐matched analysis, the two cohorts of 157 on‐clamp and 472 off‐clamp patients did not differ for all covariates, except for warm ischemia time and last estimated glomerular filtration rate. At joinpoint analysis, the off‐clamp group showed higher probabilities of maintaining an unmodified estimated glomerular filtration rate ( P  = 0.02). The probability of developing a stage ≥3b chronic kidney disease was significantly higher ( P  < 0.001) in the on‐clamp cohort. At multivariable analysis, estimated glomerular filtration rate at discharge and off‐clamp approach were independent predictors of improved functional outcomes. Perioperative complications were comparable among the two cohorts ( P  = 0.67). There were not any statistically significant differences in terms of cancer‐specific survival ( P  = 0.26) and overall survival ( P  = 0.18). Conclusions: Off‐clamp partial nephrectomy seems to offer a higher probability of maintaining 100% estimated glomerular filtration rate after surgery. In our cohort, patients undergoing on‐clamp partial nephrectomy presented a 7.3‐fold increased risk of developing a severe chronic kidney disease during follow up.